Qur'an translation : discourse, texture and exegesis. 2026-02-16T01:15:10+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Abdul-Raof, Hussein (Culture and civilization in the Middle East, 2001)

(untitled)
The Qur'an is read by millions of Muslims on a daily basis, yet there is no book available to the reader, Arab or non-Arab, which provides a linguistic and rhetorical insight into Qur'anic discourse. This book explains Qur'an translational problems and provides a thorough account of the unique syntactic, semantic, phonetic, prosodic, pragmatic, and rhetorical features of the Qur'an.--Publisher's description